Evaluating local primary health care actions to address health inequities: analysis of Australia's Primary Health Networks - Alice Windle; Sara Javanparast; Toby Freeman; Fran Baum (BMC, 2023)
Abstract Background Meso-level, regional primary health care organisations such as Australia's Primary Health Networks (PHNs) are well placed to address health inequities through comprehensive primary health care approaches. This study aimed to examine the equity actions of PHNs and identify factors that hinder or enable the equity-orientation of PHNs' activities. Methods Analysis of all 31 PHNs' public planning documents. Case studies with a sample of five PHNs, drawing on 29 original interviews with key stakeholders, secondary analysis of 38 prior interviews, and analysis of 30 internal planning guidance documents. This study employed an existing framework to examine equity actions. Results PHNs displayed clear intentions and goals for health equity and collected considerable evidence of health inequities. However, their planned activities were largely restricted to individualistic clinical and behavioural approaches, with little to facilitate access to other health and social services, or act on the broader social determinants of health. PHNs' equity-oriented planning was enabled by organisational values for equity, evidence of local health inequities, and engagement with local stakeholders. Equity-oriented planning was hindered by federal government constraints and lack of equity-oriented prompts in the planning process. Conclusions PHNs' equity actions were limited. To optimise regional planning for health equity, primary health care organisations need autonomy and scope to act on the 'upstream' factors that contribute to local health issues. They also need sufficient time and resources for robust, systematic planning processes that incorporate mechanisms such as procedure guides and tools/templates, to capitalise on their local evidence to address health inequities. Organisations should engage meaningfully with local communities and service providers, to ensure approaches are equity sensitive and appropriately targeted.